2014
DOI: 10.1136/bmj.g2622
|View full text |Cite|
|
Sign up to set email alerts
|

Annual Review of Competence Progression (ARCP) performance of doctors who passed Professional and Linguistic Assessments Board (PLAB) tests compared with UK medical graduates: national data linkage study

Abstract: Objective To determine whether use of the Professional and Linguistic Assessments Board (PLAB) examination system used to grant registration for international medical graduates results in equivalent postgraduate medical performance, as evaluated at Annual Review of Competence Progression (ARCP), between UK based doctors who qualified overseas and those who obtained their primary medical qualification from UK universities.Design Observational study linking ARCP outcome data from the UK deaneries with PLAB test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 20 publications
5
97
0
Order By: Relevance
“…In keeping with other studies22, 23, 24, 25, these results suggest that candidates who require multiple attempts at a postgraduate medical examination are more likely to struggle with other medical assessment processes (in this case, assessment via a selection process). This information may identify doctors who will require additional support through their training and guide national bodies when considering borderline candidates or appeals.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In keeping with other studies22, 23, 24, 25, these results suggest that candidates who require multiple attempts at a postgraduate medical examination are more likely to struggle with other medical assessment processes (in this case, assessment via a selection process). This information may identify doctors who will require additional support through their training and guide national bodies when considering borderline candidates or appeals.…”
Section: Discussionsupporting
confidence: 86%
“…For example, McDougle and colleagues23 compared graduates who initially failed Step 1 of the USMLE ® with those who passed it first time, finding that the relative risk of not being specialty board certified was 2·2. Multiple attempts at the Medical College Admission Test (MCAT) have also been associated with an increased risk of failing Step 2 of the USMLE ®24 , whereas multiple attempts at the Professional and Linguistic Assessments Board (PLAB) test have been shown to be independently predictive of unsatisfactory training performance25. The relationship between the number of attempts required to pass a postgraduate UK medical examination and performance in other medical assessments is unknown, but one study17 found that as the number of attempts at each part of the MRCP examination increased, final passing score decreased.…”
Section: Discussionmentioning
confidence: 99%
“…For the present study the yardstick is performance in the MRCGP and MRCP(UK) examinations, and the yardstick of the Annual Review of Competence Progression is analysed in a separate report by a different team. 25 The logic of the current study is straightforward: MRCP(UK) and MRCGP exams are taken by both UK and PLAB graduates, and if the UK and PLAB graduates are equivalent in their outcomes then they should perform equally well when they take the MRCP(UK) and MRCGP. The situation is made somewhat more complex as UK and PLAB graduates choose which medical specialty to enter, and they are also selected onto training programmes such as for general practice or for core medical training.…”
Section: Direct and Indirect Comparisonmentioning
confidence: 99%
“…Board (PLAB) exam before applying for GP specialty training. Two recent studies looking at the predictive validity of the PLAB exam in relation to MRCP and the MRCGP outcomes, 3 and Annual Review of Competence Progression outcomes in a variety of medical specialties 5 have concluded that the current standard of PLAB is set too low, and is below the competency level expected for a UK graduate completing foundation Year 1 training. Doctors who are not equivalent at entry to GP specialty training are likely to struggle with the MRCGP unless they receive training that addresses their specific needs.…”
Section: Licensing Exams and Judicial Reviewmentioning
confidence: 99%